Model Determinan Return on Asset dan Firm Value pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Sri Fitri Wahyuni; Ika Arwana (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to analyze and determine the effect of corporate social responsibility and good corporate governance toward Firm Value with return on asset as an intervening variable to the company food and beverage companies listed on the Indonesia stock exchange year 2014-2018. This research uses an associative approach. To obtain the data needed use documentation technique. Data analysis techniques in the study using panel data regression. The results of this study indicate partially that corporate social responsibility does not significantly influence return on asset. Independent board of commissioners has a significant influence on return on asset. Institutional ownership has a significant effect on return on asset. Corporate social responsibility does not significantly influence the Firm Value. The independent board of commissioners has no effect on the Firm Value. Instutional ownership does not affect the Firm Value. Return on asset does not mediate the effect of corporate social responsibility on Firm Value. Return on asset does not mediate the independent board of commissioners on Firm Value. Return on asset mediates institutional ownership of firm value.